Part-Time Work and Industry Growth - Bruce Chelimsky Fallick (Luxembourg Income Study (LIS), 1998)
The popular impression that employment in the U.S. has become more part-time in recent years may be driven by a tendency for faster-growing industries to use relatively more part-time work. This paper documents this association for the period 1983-1993, and demonstrates that it is robust to questions about how to measure industry growth and part-time intensity. A similar relationship can be discerned in several other countries. However, judging from data from the 1930s on, the association does not emerge clearly in the United States until the 1980s, suggesting that part-time work and industry growth are not intrinsically related. Moreover, both the relative growth rates and the relative part-time intensities of industries have changed markedly over the post-war period. There is no indication that part-time work at fast-growing industries is more likely to be involuntary, although this may be true for entering workers, nor has there been any trend in that direction.
Keywords: 330; Teilzeitarbeit; Wirtschaftswachstum; Industrieproduktion; USA